Strategi Komunikasi Pemasaran Media Digital Instagram Coffee Shop Bata Mera Coffee & Cascara dalam Meningkatkan Loyalitas Konsumen - Putra, Aldi Renaldy Hadi; Sari, Eka Anisa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Businesses are becoming more competitive in the age of globalization. Consequently, the company will be unable to compete with its rivals if it does not employ an effective marketing plan. Businesses utilize effective communication to remind, educate, and convince consumers about the goods they plan to sell, either directly or indirectly. The data gathered by the researcher includes a description of the scenario from field notes, interview manuscripts, and personal papers. The nature of this study is qualitative and descriptive. This researcher uses a qualitative approach, so in this research it aims to match the phenomenon being studied with the STP (Segmentation, Targeting, and Positioning) theory. Thus, it can be concluded that the marketing communication plan implemented by Bata Mera coffee & Cascara is to use Instagram social media promotion by using STP theory to increase consumer loyalty. From various posts, whether it is education related to the mainstay product knowledge of Bata Mera coffee & Cascara or activities that occur in Bata Mera coffee & Cascara.